TINJAUAN YURIDIS TERHADAP PELAKU TINDAK PIDANA PENIPUAN DENGAN MODUS PENYALAHGUNAAN NAMA PEJABAT NEGARA YANG DI LAKUKAN DALAM UPAYA PENERIMAAN TARUNA AKADEMI KEPOLISIAN - Hakim, Lukmanul; ., Anggalana; Wijaya, Zullya (Bahasa Indonesia, 2024)
Global law enforcement requires the role of the police as representatives of the state, with varying duties in each country. In Indonesia, the National Police (Polri) serves a dual function as law enforcer and social worker. Becoming a police officer is an attractive choice, especially for the younger generation, as it is regarded as a noble profession and an educational alternative. However, admission to the Police Academy (Akpol) has a limited quota, which puts pressure on prospective cadets. Some candidates fall victim to fraud schemes involving the misuse of the names of state officials. This research examines such fraudulent crimes using the case study of Decision Number 377/Pid.B/2023/PN.Tjk. The case involves defendants who used false names to obtain funds from prospective cadets. This study aims to provide insights into the penalties for perpetrators of such crimes and contribute to protecting the integrity of the admission process in police education institutions.